TUBERCULOSIS IN CHILDREN IN IRKUTSK REGION - Ye. Yu. Zorkaltseva; S. V. Pugacheva; I. Yu. Chukavina (Бюллетень сибирской медицины)
Epidemiology situation and factors its determinates was analyzed. Reports of tuberculosis hospitals used and results of observed two hundred and sixty-three children with tuberculosis. It was determinate that reasons of increase children morbidity of tuberculosis: bad epidemiology situation in adults in region, not all adult patients with tuberculosis was hospitalized, defects of prophylactic of tuberculosis. Tuberculosis in children having contact with tuberculosis was determinates earlier and structure of clinical forms was better than in children which have no contact.